Radio Resources Allocation Based-on Energy Saving For Lte-advanced System - Vinsensius Sigit Widhi Prabowo; Arfianto Fahmi; Doan Perdana (eProceedings of Engineering, 2017)
With increasing demand for faster access, then LTE-Advance system (LTE-A) is developed dan released by the fourth generation (4G) mobile system. 3GPP introduced a new technology that is Carrier Aggregation (CA) to support wider transmission bandwidth and spectrum efficiency. With the CA system, every user can be scheduled on multiple carriers. Because of the difference in frequencies for each carrier, there are some differences too in fading and coverage for each carrier. This problem effects the performance of conventional resources allocation algorithm especially mean-greedy algorithm. Then a method to classify users and chunk according to the number of carriers that can be given to the user is proposed. This process is called user chunk grouping (UCG). This process is performed before the mean-greedy algorithms process. Each user is grouped based on the characteristics of each component carrier fading experienced by the user. This scheme is expected to overcome the problem caused by CA system. Through simulation process, the UCG process can improve either fairness system or average throughput according to the ratio of user and bandwidth used in system. Keywords: Carrier Aggregation, Mean-Greedy, User Grouping, LTE-